ANALISIS PENYEBAB KESALAHAN PENULISAN HURUF KATAKANA PADA MAHASISWA ANGKATAN 2020 PROGRAM STUDI PENDIDIKAN BAHASA JEPANG - Asri Rahmawika. H; Nana Rahayu; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study contains the analysis of writing errors of katakana in students of the Japanese language education study program. The problem that will be discussed in this study is the cause of writing errors in katakana. The purpose of this study is to describe the causes of writing errors in katakana. The method used in this study is a qualitative descriptive method. The data sources used in this study are the Class of 2020 students, totaling 27 people and the data obtained by 6 students. Data collection technique in this research is interview. The data analysis technique is described based on the Shah's theory. From the results of interview research, it was found that motivation and interest in studying katakana were the cause of the writer's error.Key Word: Analysis, katakana.